2014
DOI: 10.5588/pha.14.0023
|View full text |Cite
|
Sign up to set email alerts
|

Sputum smear conversion and treatment outcomes for tuberculosis patients with and without diabetes in Fiji

Abstract: Fiji is a low tuberculosis (TB) burden country, with a TB incidence rate of 24 cases per 100 000 population and a high treatment success rate of 90% (2012 data). 1 However, diabetes mellitus (DM) is very common in Fiji, and its prevalence is thought to be increasing. The STEPwise approach to Surveillance (STEPs) study conducted in 2002 reported a population prevalence of 16% for DM. 2 A more recent estimate, using a different methodology, gave a DM prevalence among adults in Fiji of 10.9%, with impaired gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
5
11
0
Order By: Relevance
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 57%
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 57%
“…Magee et al found no difference in culture conversion between patients in Georgia with MDR-TB + DM and patients with MDR-TB (adjusted hazard ratio [aHR] 0.95, 95% CI 0.71-1.28 [12]. Similar results have been reported in studies conducted in Morocco [13], the United States [14], India [15], Fiji [16] and in a multinational study that included MDR-TB patients from Peru, Estonia, Russia and the Philippines [17].…”
Section: Discussionsupporting
confidence: 73%
“…Previously, it has been described that TB-DM co-morbidity could result in higher susceptibility to TB [1,42], more severe clinical symptoms, and slower responses to anti-TB treatment including delayed sputum-culture conversion [6,7,[44][45][46]. However, a few other studies reported no differences in sputum conversion rates or nal treatment outcome between TB and TB-DM patients after anti-TB therapy [9,10]. In the present study, sputum or culture conversion was not delayed in TB-DM patients compared to TB patients, and accordingly treatment outcome did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that at the end of 2 months intensive phase anti-TB treatment diabetic TB patients are sputum positive more often than TB patients without DM [4][5][6][7][8] . However in contrast, other studies failed to detect differences between TB-DM and TB patients in sputum smear or culture conversion [9,10]. TB-DM co-morbidity at the time of TB diagnosis has frequently been associated with a hyper-in ammatory cytokine pro le [11,12], and recently a plasma biomarker assay demonstrated that this systemic in ammatory state persisted in TB-DM patients throughout effective anti-TB treatment [13].…”
Section: Introductionmentioning
confidence: 99%